Growth, characterization and gas sensing properties of one dimensional oxide nanostructures on Ti and Ti-6Al-4V alloy substrates synthesized by thermal oxidation / Md. Arafat Mahmood - Md. Arafat, Mahmood (2017)
One dimensional (1-D) nanostructures of titanium dioxide (TiO2) are of particular interest due to their capabilities of being used as functional materials in various applications such as mesoscopic physics and nanoscale devices. Wide variety of fabrication routes such as hydrothermal, electrospinning, anodization, UV lithography and thermal oxidation have been developed for synthesizing TiO2 nanostructures. Among all these routes, thermal oxidation is attractive for mass production due to its simplicity, scalability and low production cost. In this research work, 1-D nanostructures of TiO2 were synthesized on pure Ti and Ti-6Al-4V (Ti64) substrates by thermal oxidation. The oxidation parameters were optimized by investigating the effects of alloy microstructure, temperature, oxidation atmosphere, gas flow rate, residual stress and oxidation duration. The resultant nanostructures were investigated using X-ray diffractometer, X-ray photoelectron spectroscope, Raman spectroscope, transmission electron microscope, scanning electron microscope etc. For the preparation of gas sensors, Ti and Ti64 particles were deposited on Au interdigitated alumina substrates and thermally oxidized under optimum conditions for the growth of 1-D nanostructures. The as-prepared sensors were exposed to different target gases including H2, H2S, CO, CH4, CH3OH, C2H5OH, C2H4, NO2 and O2. The ratio of the electrical resistance in the background and the target gas environment was used to denote the sensing response of the sensors. Results revealed that during thermal oxidation oxide scales were formed on the Ti and Ti64. The 1-D nanostructures were evolved from the top surface of the oxide scales at 750 °C in oxygen deprived conditions (<100 ppm O2 in Ar). The presence of residual stress inside Ti and Ti64 significantly improved the coverage of 1-D nanostructures. New surfaces were formed in the form of 1-D nanostructures due to the relaxation of residual stress during thermal oxidation. The 1-D nanostructures on pure Ti were rutile TiO2 and they formed in moist Ar environment. TiO2 scale was formed beneath the 1-D nanostructures. On the other hand, 1-D core-shell TiO2-Al2O3 nanostructures were formed during thermal oxidation of Ti64 in the presence of tens of ppm O2 in flowing dry Ar. A double layer of oxide scales was formed beneath the 1-D nanostructures. The top oxide scale is a mixture of TiO2 and Al2O3 whereas the inner oxide scale is only TiO2. It is proposed that during thermal oxidation metal ions diffuse in the outward direction and reacts with the oxygen containing species at [0 0 2] crystallographic direction of rutile to form 1-D nanostructures. The gas sensing results showed that the optimum operating temperature of the sensor was 650 °C and possessed selective response towards H2S, CH3OH and C2H5OH. However, the highest response of 1109 was seen for 1000 ppm C2H5OH at 650 °C. Due to the catalytic activity of 1-D nanostructures, C2H5OH was decomposed and an amorphous layer of carbon was deposited on the nanostructures. Deposition of amorphous carbon significantly reduced the resistance of the sensor which is the reason for high selective response towards C2H5OH. The sensor showed complete recovery during the exposure in background environment.